2017
DOI: 10.13104/imri.2017.21.2.102
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Decrease in γ-AminoButyric Acid after Caffeine Intake in Adolescents: a Preliminary MRS Study

Abstract: In adolescents, sleep deprivation problem is getting worse, and increased caffeine consumption is considered to relieve the stress caused by sleep deprivation and academic burden. In this study, immediate neurologic effects of caffeine intake on adolescents were evaluated in three high school students using the γ-aminobutyric acid (GABA)/creatine ratio on magnetic resonance spectroscopy (MRS). MEGA-PRESS MRS and TE 135 ms single voxel MRS were performed in the anterior cingulate cortex before and after drinkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Current result of GABA neurotransmitter goes along with results of Almehmadi, (2017) study which showed significant decrease in GABA levels in different brain regions after three weeks of a similar dose to our used dose , and this is explained by caffeine suppression of GABAergic pathways (Alasmari, 2020) through postsynaptic and presynaptic mechanisms, post-synaptically by caffeine blockage of GABAergic inhibitory postsynaptic currents and pre-synaptically through decrease of GABA release by increasing intra cellular calcium through activation of cyclic nucleotide-gated calcium permeable channels which activated by cyclic adenosine monophosphate, cyclic guanosine monophosphate that increased by caffeine (Isokawa, 2016) This study results coincided with results of Hahn et al, (2015) which observed decrease of GABA release by measuring GABA levels by magnetic resonance spectroscopy after intake of caffeine in adolescents which sounded to be the cause for anxiety or excitement in adolescents following caffeine intake.…”
Section: Discussionsupporting
confidence: 87%
“…Current result of GABA neurotransmitter goes along with results of Almehmadi, (2017) study which showed significant decrease in GABA levels in different brain regions after three weeks of a similar dose to our used dose , and this is explained by caffeine suppression of GABAergic pathways (Alasmari, 2020) through postsynaptic and presynaptic mechanisms, post-synaptically by caffeine blockage of GABAergic inhibitory postsynaptic currents and pre-synaptically through decrease of GABA release by increasing intra cellular calcium through activation of cyclic nucleotide-gated calcium permeable channels which activated by cyclic adenosine monophosphate, cyclic guanosine monophosphate that increased by caffeine (Isokawa, 2016) This study results coincided with results of Hahn et al, (2015) which observed decrease of GABA release by measuring GABA levels by magnetic resonance spectroscopy after intake of caffeine in adolescents which sounded to be the cause for anxiety or excitement in adolescents following caffeine intake.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, caffeine has been found to decrease the activity of the γ-aminobutyric acid (GABA) ergic system and modulate GABA receptors, leading to neurobehavioral effects [ 201 ]. Chronic caffeine intake may be related to long-term decrease in GABA [ 210 ].…”
Section: Coffee and The Brain–gut Axismentioning
confidence: 99%